Developing a Hybrid Learning Model Based on Moodle E-Learning on Morphology Course - Abdullah, Abdullah; Talib, Ahmad; Abduh, Amirullah (Tamaddun Life, 2022)
This study aimed to develop a hybrid learning model and design instructional material for the Morphology course at Makassar State University's Faculty of Languages and Literature in order to develop students' knowledge of linguistic theories and skills, in particular those pertaining to the English language. These improvements were intended to benefit students in the English department. Following a research design and development model that has been designed will be the development of a learning model and the design of instructional content. This study is an extensive process that designs the needs of students and develops the product or course material of morphology to increase the ability or skills of students in learning language through hybrid learning based on moodle. Specifically, this research focuses on the development of a hybrid learning environment (e-learning). Students enrolled in the English department of the Faculty of Languages and Literature at the State University of Makassar are the subjects of this study's population. The participants in the English Education and Literature Study Program would serve as the sample for this investigation. The findings of the study indicate that there may be a hint of a hybrid learning model based on student worksheet activities or exercises, Syllabus, design instructional material for a morphology course, and moodle e-learning. The findings of the study implicate on the pedagogical practice of Moodle e-learning within an EFL hybrid learning setting.